A Short Note on the Distribution of Grasses and Sedges of the Buxa Division, West Bengal - Chaudhuri, A. B. (Indian Forester, 1959)
The distribution of the common grasses and a few sedges in the Riverain forests, Evergreen forests, Sal forests, Wet mixed forests and Dry mixed forests of the Buxa division, West Bengal and some aspects of their ecology have been noted in a broad outline. Grasslands of this division occur only in the moisture pockets and have been classified as high and low level savannahs. Evergreen species, due to fire protection, filled up the savannah areas and invaded the sal forests ousting the grasses. Extensive grasslands are therefore not found anywhere except in the Bholka range where tree forests died as a result of flood. Common grasses of the roadsides, lawns and clearings have also been noted and their habitats discussed in brief.